A graphite negative electrode material and its preparation method and use
By using strong shearing equipment in graphite negative electrode materials for solid phase coating, the problem of poor uniformity of the carbon layer coating of graphite negative electrode materials is solved, the electrochemical performance and fast charging performance are improved, and the production efficiency is improved.
Patent Information
- Application Number
- CN202111245140.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-26
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-10-26
AI Technical Summary
In the prior art, the carbon layer coating uniformity of graphite negative electrode materials leads to poor electrochemical performance, insufficient rate performance, and low production efficiency of conventional solid-phase coating processes and poor performance stability.
Using a device with strong shearing effect, soft solid-phase coating particles are rubbed and mixed with graphite particles. Through the primary and secondary mixing process, the thin layer of the solid-phase coating particles is peeled off and adhered to the graphite surface to achieve denseness. Uniform carbon coating.
The first-effect and rate-efficiency performance of graphite negative electrode materials has been significantly improved, the fast charging performance has been improved, the first-effect of the battery has reached more than 87.32%, the fast-recharge performance of 2C/0.2C has reached more than 29%, and the production efficiency has been optimized.
Smart Images

Figure BDA0003320692140000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] In the 1980s, the concept of rocking chair battery was proposed, and then carbon negative electrode lithium-ion battery began to sprout. Graphite is different from low-temperature carbonized negative electrode materials. Due to high-temperature treatment, there are fewer heteroatoms and defects in graphite negative electrode materials, so the coulomb efficiency is as high as over 90%. In addition, its high degree of graphitization makes the lithium storage mechanism of graphite negative electrode intercalation, so its discharge platform is broad, which is conducive to product use. The theoretical capacity of natural graphite and artificial graphite negative electrode materials is 372mAh / g. The capacity of the excellent graphite negative electrode materials currently on the market can reach 365mAh / g, so graphite has become an excellent negative electrode material in lithium batteries.
[0003] However, graphite anode materials, which use intercalation as the main lithium storage mechanism, have poor rate performance because lithium ions can only be deintercalated along the direction of graphite sheets. In button cells, the rate generally does not exceed 3C. In response to this, using coating agents to coat and modify the graphite surface to construct an isotropic thin carbon layer to increase the pathway for lithium ions to enter the graphite has become the mainstream method of modifying graphite anode materials on the market.
[0004] In industrial production, solid phase coating is the most commonly used coating method with simple process and high production efficiency. However, conventional solid phase coated products have poor uniformity, general coating effect and poor performance stability of the products produced.
[0005] CN102255076A discloses a graphite material with a surface coated carbon layer, a preparation method and an application as a negative electrode material for lithium-ion batteries. The method comprises: A. Fully mixing the carbon source as a coating with graphite powder at a mass ratio of 10:100; the carbon source as a coating is phenolic resin powder and petroleum asphalt powder at a mass ratio of 1:1, and the graphite powder is natural graphite powder that has been sphericalized; the temperature of the mixture is controlled to rise to 120 degrees Celsius, and stirring is maintained at this temperature for 3 hours; B. The product of step A is completely carbonized for 12 hours at a temperature of 1100 degrees under an argon protection environment; the obtained product is crushed and graded, and a product with a particle size D50 of 20um is screened out; C. The product of step B is graphitized at a temperature of 2400 degrees for 72 hours. The document is a conventional method for coating graphite with solid phase carbon, which will result in poor uniformity of the coated product, general coating effect, and poor performance stability of the produced product.
[0006] CN103647055A discloses an epoxy resin modified graphite negative electrode material and a preparation method thereof. An epoxy resin modified natural graphite material is obtained by grinding, high temperature curing, carbonizing and crushing an organosilicon modified epoxy resin and natural graphite. Although the co-embedding of large volume solvent molecules can be prevented, high temperature pyrolysis is prone to agglomeration, and crushing will also destroy the coating effect, resulting in uneven coating on the graphite surface and destruction of the coating layer, and ultimately failing to achieve a good coating effect.
[0007] Therefore, how to make the carbon layer evenly and densely coated on the surface of the graphite material, thereby improving the electrochemical performance of the graphite negative electrode material, is a technical problem that needs to be solved urgently. Summary of the invention
[0008] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a graphite negative electrode material, preparation method and use. The present invention uses a device with strong shearing effect to rub and fully mix relatively soft solid-phase coating agent particles with graphite particles. Due to the strong shearing and friction, the thin layer on the surface of the solid-phase coating particles gradually falls off, and because of the good wettability of graphite and the coating particles, they adhere to the surface of graphite, thereby greatly improving the coating effect of the solid-phase coating agent on graphite, making the carbon layer densely and evenly coated, thereby improving the first effect and rate performance of the graphite negative electrode material, and at the same time, its fast charging performance is also significantly improved.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing a graphite negative electrode material, the preparation method comprising:
[0011] The graphite and the solid-phase coated particles are mixed once, and then mixed again by shear force, and carbonized to obtain the graphite negative electrode material;
[0012] The solid-phase coated particles are made of a material having a softening point of 40 to 300°C. For example, the softening point may be 40°C, 50°C, 100°C, 150°C, 200°C, 250 or 300°C.
[0013] The present invention adopts equipment with strong shearing effect to rub and fully mix relatively soft solid-phase coating agent particles with graphite particles. Due to the strong shearing and friction, the thin layer on the surface of the solid-phase coating particles gradually falls off, and due to the good wettability of graphite and the coating particles, the solid-phase coating particles adhere to the graphite surface, thereby greatly improving the coating effect of the solid-phase coating agent on the graphite, so that the carbon layer is densely and evenly coated, thereby improving the first effect and rate performance of the graphite negative electrode material. The preparation method provided by the present invention can realize continuous production, and has higher production efficiency than the traditional "one-pot" solid-phase coating process.
[0014] In the present invention, solid-phase coated particles with a softening point of 40 to 300° C. are selected, and with the aid of a strong shear force, the solid-phase coated particles can be better peeled off and attached to the graphite surface. The softening point should be ≥40° C. to avoid melting into a liquid state during processing. If the softening point is less than 40° C., the solid-phase coated particles will soften due to frictional heat generation, thereby causing graphite agglomeration, which is not conducive to the uniform dispersion of the solid-phase coated particles and brings too high a load to the device drive motor. The softening point of the solid-phase coated particles needs to be further ≤300° C. to avoid weakening the wettability of the soft carbon precursor and graphite due to too few small molecules in its components, and causing the coating agent to have a large viscosity and be difficult to spread on the graphite surface due to the small number of small molecules in the carbonization process.
[0015] In the present invention, if only one mixing is performed without a second mixing, the solid-phase coated particles and the graphite will be in a simple mixed state, resulting in the inability to evenly coat the graphite when the solid-phase coated particles soften during the subsequent carbonization process; and if only a second mixing is performed without a first mixing, it will be difficult to evenly disperse the solid-phase coated particles in the graphite, resulting in the final product being a mixture of soft carbon and graphite.
[0016] The preparation method provided by the present invention has a preparation environment of: temperature not higher than 40°C and humidity less than 75%, under which the solid phase coating agent can maintain its morphology well. In a poor processing environment, such as when the humidity is high, the solid phase coating agent is easy to absorb water and agglomerate, resulting in poor processing performance and poor product performance; when the temperature is high, the solid phase coating agent is easy to become sticky and agglomerate, which is not conducive to the preparation of the final product.
[0017] Preferably, the method for preparing the graphite negative electrode material is carried out under a protective atmosphere or under hot air conditions.
[0018] Preferably, the solid-phase coated particles are asphalt materials.
[0019] In the present invention, asphalt material is selected as the solid-phase coating particles, and with the help of strong shear force, the solid-phase coating particles can be better peeled off and attached to the graphite surface. Compared with other coating materials such as epoxy resin, it has the advantages of convenient storage and use, simple raw material crushing, high carbonization rate, and regular carbide carbon layer. The asphalt material must be in a solid state during the processing process, so its softening point must be ≥40°C to avoid melting into a liquid state during the processing. If its softening point is less than 40°C, the solid-phase coating particles will soften due to frictional heat, which will lead to graphite agglomeration, which is not conducive to the uniform dispersion of the solid-phase coating particles and brings too high a load to the equipment drive motor; the softening point of the asphalt material needs to be further ≤300°C, so as not to weaken the wettability of the soft carbon precursor and graphite due to too few small molecules in its components, and the coating agent has a large viscosity due to the small number of small molecules in the carbonization process, making it difficult to spread on the graphite surface.
[0020] Preferably, the softening point of the solid-phase coated particles is 50-150°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.
[0021] Preferably, the median particle size of the solid-phase coated particles is 2 to 10 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.
[0022] Preferably, the graphite includes artificial graphite and / or natural graphite.
[0023] Preferably, the asphalt material includes any one of petroleum asphalt, coal asphalt or artificial asphalt, or a combination of at least two of them.
[0024] Preferably, the mass ratio of the solid-phase coated particles to graphite is (5-20):(95-80), for example, 5:95, 10:90, 15:85 or 20:80.
[0025] Preferably, the time for the primary mixing is 5 to 30 min, for example, 5 min, 10 min, 15 min, 20 min, 25 min or 30 min.
[0026] In the present invention, within the above-mentioned one-time mixing time range, the solid phase of the material can be better dispersed uniformly.
[0027] Preferably, the primary mixing is performed by a mixing device.
[0028] In the present invention, the mixing equipment includes but is not limited to a homogenizing and dispersing barrel, a high-speed mixer, a zero-gravity mixer, a V-type mixer or a VC high-efficiency mixer.
[0029] Preferably, the mixing frequency of the mixing device is 20 to 50 Hz, for example, 20 Hz, 25 Hz, 30 Hz, 35 Hz, 40 Hz, 45 Hz or 50 Hz.
[0030] Preferably, the secondary mixing by shear force comprises any one of high-speed stirring, kneading or screw extrusion or a combination of at least two thereof, preferably screw extrusion.
[0031] In the present invention, the shearing force is realized by screw extrusion, which is more conducive to the cohesive failure of the solid-phase coated particles due to the strong shearing force, so that they are continuously peeled off.
[0032] Preferably, the screw extrusion is performed by a mixing device with a screw.
[0033] Preferably, the rotation speed of the mixing device with a screw is 60 to 300 rpm, for example, 60 rpm, 80 rpm, 100 rpm, 130 rpm, 150 rpm, 180 rpm, 200 rpm, 230 rpm, 250 rpm, 280 rpm or 300 rpm.
[0034] In the present invention, if the rotation speed of the mixing device with a screw is too low, the shear force applied to the solid-phase coated particles is small, and the solid-phase coated particles cannot be effectively destroyed, resulting in uneven coating. If the rotation speed is too high, in addition to affecting the life of the equipment, the excessively high rotation speed will also cause the temperature during the mixing process to be too high. The excessively high temperature will cause the solid-phase coated particles to soften into a liquid state, causing graphite to agglomerate and causing the screw torque to increase sharply, which can easily cause damage to the equipment.
[0035] Preferably, the mixing device with a screw comprises an inlet end, a compacting section, a shearing section and a discharge end in sequence.
[0036] In the present invention, the thread pitch at the feeding end is relatively wide to ensure that the material can smoothly enter the equipment chamber; the thread pitch of the compacting section is gradually shortened to ensure that the material is tightly compacted; the shearing section is the stage where the mixing equipment plays a major role in strong shearing and friction. Under the strong shearing and friction, the friction between the solid-phase coated particles and the graphite particles gradually increases, and the surface layer and the inner layer of the soft solid-phase coating agent are continuously peeled off and fallen off due to the large shearing force. In addition, because the components of the solid-phase coating agent are oleophilic and have good graphite infiltration performance, the solid-phase coating agent can be well attached to the uneven graphite surface, thereby achieving the effect of uniformly coating the graphite surface; the fourth section is the discharging end, and the screw pitch of this section is gradually widened, so that the material becomes fluffy under the continuous stirring external force, which is convenient for material discharge.
[0037] Preferably, the thread pitch of the feeding end is smaller than the thread pitch of the compacting section.
[0038] Preferably, the carbonization temperature is 900-1200°C, such as 900°C, 1000°C, 1100°C or 1200°C.
[0039] Preferably, the carbonization time is 5 to 10 h, for example, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.
[0040] Preferably, after the carbonization, the carbonized product is sequentially depolymerized and screened, and the screening equipment used is one or more of an ultrasonic vibrating screen, an oscillating screen, and a rotary vibrating screen, and the filter screen is selected to be 200 to 500 meshes, such as 200 mesh, 300 mesh, 400 mesh or 500 mesh.
[0041] As a preferred technical solution, the preparation method comprises:
[0042] The graphite and the solid-phase coated particles are mixed once for 5 to 30 minutes at a mass ratio of (95 to 80): (5 to 20) by a mixing device at a mixing frequency of 20 to 50 Hz, and then mixed twice by a mixing device with a screw by screw extrusion at a speed of 60 to 300 rpm under the action of shear force, and carbonized at 900 to 1200° C. for 5 to 10 hours to obtain the graphite negative electrode material;
[0043] The solid-phase coated particles are asphalt materials, which include any one of petroleum asphalt, coal asphalt or artificial asphalt, or a combination of at least two of them, and the softening point of the asphalt material is 50-150°C.
[0044] In a second aspect, the present invention provides a graphite negative electrode material, wherein the graphite negative electrode material is prepared by the method for preparing the graphite negative electrode material as described in the first aspect, and the graphite negative electrode material is a graphite surface coated with a carbon coating layer.
[0045] In a third aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the graphite negative electrode material as described in the second aspect.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] The present invention adopts equipment with strong shearing effect to rub and fully mix relatively soft solid-phase coating agent particles with graphite particles. Due to the strong shearing and friction, the thin layer on the surface of the solid-phase coating particles gradually falls off, and due to the good wettability of graphite and the coating particles, the solid-phase coating particles adhere to the graphite surface, thereby greatly improving the coating effect of the solid-phase coating agent on the graphite, so that the carbon layer is densely and evenly coated, thereby improving the first efficiency and rate performance of the graphite negative electrode material, and at the same time, its fast charging performance is also significantly improved, so that the first efficiency of the battery is above 87.32%, and its 2C / 0.2C fast charging performance is above 29%. The screw extrusion speed is further adjusted so that it is within the preferred range, and its 2C / 0.2C fast charging performance can reach more than 31%. DETAILED DESCRIPTION
[0048] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0049] Example 1
[0050] This embodiment provides a method for preparing a graphite negative electrode material, and the preparation method is as follows:
[0051] Artificial graphite (median particle size of 16 μm) and petroleum asphalt (softening point of 50°C, median particle size of 5 μm) were mixed once in a V-type mixer at a mass ratio of 95:5 at a mixing frequency of 30 Hz for 25 min;
[0052] Then, a secondary mixing is carried out by screw extrusion at a rotation speed of 60 rpm through a mixing device with a pair of screws, and the mixture after the primary mixing is fed into the feeding end of the mixing device with a pair of screws into the equipment chamber, and the material is compacted in turn through the compacting section, and then the artificial graphite is coated with petroleum asphalt in the shearing section, and then the material is discharged through the discharging end, and then carbonized at a carbonization temperature of 1000°C for 10 hours, the carbonized product is depolymerized, and a 200-mesh sieve is used for screening to obtain a graphite negative electrode material with a carbon coating layer on the surface.
[0053] Example 2
[0054] Natural graphite (median particle size of 12 μm) and coal tar pitch (softening point of 150°C, median particle size of 9 μm) were mixed once in a homogenizing dispersion barrel at a mass ratio of 80:20 at a mixing frequency of 50 Hz for 10 min;
[0055] Then, a secondary mixing is carried out by screw extrusion at a rotation speed of 300 rpm through a mixing device with a pair of screws, and the mixture after the primary mixing is fed into the feeding end of the mixing device with a pair of screws into the equipment chamber, and the material is compacted in turn through the compacting section, and then the natural graphite is coated with coal tar in the shearing section, and then the material is discharged through the discharging end, and then carbonized at a carbonization temperature of 1200°C for 5 hours, the carbonized product is depolymerized, and a 500-mesh sieve is used for screening to obtain a graphite negative electrode material with a carbon coating layer on the surface.
[0056] Example 3
[0057] Artificial graphite (median particle size of 15 μm) and artificial asphalt (softening point of 210°C, median particle size of 5 μm) were mixed once in a homogenizing dispersion barrel at a mass ratio of 90:10 for 30 min at a mixing frequency of 20 Hz;
[0058] Then, a secondary mixing is carried out by screw extrusion at a rotation speed of 180 rpm through a mixing device with a pair of screws, and the mixture after the primary mixing is fed into the feeding end of the mixing device with a pair of screws into the equipment chamber, and the material is compacted in turn through the compacting section, and then the natural graphite is coated with coal tar in the shearing section, and then the material is discharged through the discharging end, and then carbonized at a carbonization temperature of 900°C for 6 hours, the carbonized product is depolymerized, and a 300-mesh sieve is used for screening to obtain a graphite negative electrode material with a carbon coating layer on the surface.
[0059] Example 4
[0060] The difference between this embodiment and embodiment 1 is that in this embodiment, during the screw extrusion process, the rotation speed is 500 rpm.
[0061] The rest of the preparation methods and parameters were the same as those in Example 1.
[0062] Comparative Example 1
[0063] The difference between this comparative example and Example 1 is that coal tar is used in this comparative example, and its softening point is 350° C. and the median particle size is 5 μm.
[0064] The rest of the preparation methods and parameters were the same as those in Example 1.
[0065] Comparative Example 2
[0066] The difference between this comparative example and Example 1 is that in this comparative example, only one mixing is performed, that is, the solid-phase coated particles and graphite are mixed using a VC high-efficiency mixer at a frequency of 40 Hz for 30 minutes, and no secondary mixing is performed.
[0067] The rest of the preparation methods and parameters were the same as those in Example 1.
[0068] Comparative Example 3
[0069] The difference between this comparative example and Example 1 is that in this comparative example, only secondary mixing is performed, and primary mixing is not performed.
[0070] The rest of the preparation methods and parameters were the same as those in Example 1.
[0071] (1) Preparation of test samples: The graphite negative electrode materials provided in Examples 1-4 and Comparative Examples 1-3 were mixed with styrene-butadiene rubber, sodium carboxymethyl cellulose, and conductive carbon black in a ratio of 94.5:2.5:1.5:1.5 to prepare negative electrode sheets, and the positive electrode material was a lithium sheet; then, the sheets were pulped, coated, baked, rolled, punched, weighed, assembled, and activated to obtain button cells for testing, and electrochemical performance tests were performed;
[0072] (2) First charge and discharge reversible capacity test: Use the Arbin blue power tester to test the first charge and discharge performance of the button cell at a rate of 0.02C.
[0073] (3) First coulombic efficiency: The ratio of the first discharge capacity to the first charge capacity is calculated from the test results in (2).
[0074] (4) 2C / 0.2C fast charging performance: Using the Arbin blue battery tester, after the button battery has been cycled for 2 weeks, its discharge performance at 0.2C and 2C rates is tested, and the ratio of the latter to the former is calculated.
[0075] The results are shown in Table 1.
[0076] Table 1
[0077]
[0078] From the data results of Example 1 and Example 4, it can be seen that if the rotation speed is too fast during the secondary mixing process, the feeding speed will be reduced to prevent the screw from locking during the modification process, which will ultimately cause the equipment cavity to be unable to be effectively filled, thereby reducing the shear effect between the solid-phase coated particles and the graphite and weakening the coating effect.
[0079] It can be seen from the data results of Example 1 and Comparative Example 1 that the softening point of the solid-phase coated particles is too high, which is not conducive to the solid-phase coated particles being peeled off due to shear force and effectively adhering to the graphite surface. Moreover, during the carbonization process, the solid-phase coated particles have a large viscosity during the heating process and general spreading performance, which ultimately leads to a poor coating effect.
[0080] It can be seen from the data results provided by Example 1 and Comparative Example 2 that, compared with the traditional solid phase coating method, the graphite negative electrode material obtained by the preparation method provided by the present invention has better 2C / 0.2C fast charging performance.
[0081] It can be seen from the data results of Example 1 and Comparative Example 3 that in the present invention, only secondary mixing is performed, which will result in uneven mixing of the carbonization precursor, ultimately leading to the carbonization product being a simple blend of soft carbon and graphite, and its first efficiency and 2C / 0.2C fast charging performance are relatively low.
[0082] In summary, the present invention adopts equipment with strong shearing effect to rub and fully mix the relatively soft solid-phase coating agent particles with the graphite particles. Due to the strong shearing friction, the thin layer on the surface of the solid-phase coating particles gradually falls off, and due to the good wettability of graphite and the coating particles, they adhere to the surface of graphite, thereby greatly improving the coating effect of the solid-phase coating agent on the graphite, so that the carbon layer is densely and evenly coated, thereby improving the first efficiency and rate performance of the graphite negative electrode material, and at the same time, its fast charging performance is also significantly improved, so that the first efficiency of the battery is above 87.32%, and its 2C / 0.2C fast charging performance is above 29%. The screw extrusion speed is further adjusted so that it is within the preferred range, and its 2C / 0.2C fast charging performance can reach more than 31%.
[0083] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a graphite negative electrode material, characterized in that: The preparation method comprises: The graphite and the solid-phase coated particles are mixed once, and then mixed again by shear force, and carbonized to obtain the graphite negative electrode material; The softening point of the solid-phase coated particles is 40-300°C; the solid-phase coated particles are asphalt materials; the asphalt materials are in a solid state during processing; The secondary mixing method by shear force includes screw extrusion; the screw extrusion is performed by a mixing device with a screw; the rotation speed of the mixing device with a screw is 60-300 rpm; The mixing device with a screw comprises an inlet end, a compacting section, a shearing section and a discharge end in sequence; The thread pitch of the feeding end is smaller than the thread pitch of the compacting section.
2. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The softening point of the solid-phase coated particles is 50-150°C.
3. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The median particle size of the solid-phase coated particles is 2-10 μm.
4. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The graphite includes artificial graphite and / or natural graphite.
5. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The asphalt material includes any one of petroleum asphalt, coal asphalt or artificial asphalt, or a combination of at least two of them.
6. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The mass ratio of the solid-phase coated particles to graphite is (5-20): (95-80).
7. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The time of the first mixing is 5 to 30 minutes.
8. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The primary mixing is performed by a mixing device.
9. The method for preparing a graphite negative electrode material according to claim 8, characterized in that: The mixing frequency of the mixing device is 20-50 Hz.
10. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The carbonization temperature is 900-1200°C.
11. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The carbonization time is 5 to 10 hours.
12. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The preparation method comprises: The solid-phase coated particles and graphite are mixed once for 5 to 30 minutes at a mass ratio of (5 to 20): (95 to 80) by a mixing device at a mixing frequency of 20 to 50 Hz, and then mixed twice by a mixing device with a screw by screw extrusion at a speed of 60 to 300 rpm under the action of shear force, and carbonized at 900 to 1200° C. for 5 to 10 hours to obtain the graphite negative electrode material; The solid-phase coated particles are asphalt materials, which include any one of petroleum asphalt, coal asphalt or artificial asphalt, or a combination of at least two thereof, and the softening point of the asphalt material is 50-150°C.
13. A graphite negative electrode material, characterized in that: The graphite negative electrode material is prepared by the method for preparing a graphite negative electrode material according to any one of claims 1 to 12, and the graphite negative electrode material is a graphite surface coated with a carbon coating layer.
14. A lithium ion battery, characterized in that: The lithium-ion battery comprises the graphite negative electrode material as claimed in claim 13.
Citation Information
Patent Citations
Graphite material coated with carbon layer on surface and preparation method and application thereof
CN102255076A
Graphite cathode material modified by epoxy resin and its preparation method
CN103647055A
Rapidly-charged graphite lithium ion battery anode material and preparation method thereof
CN105024043A
Graphite negative material of lithium ion battery and producing method thereof
CN1585172A